A public expenditure review of social protection programs in the Philippines - Charlotte Justine Diokno-Sicat; Ma. Alma P. Mariano (Philippine Institute for Development Studies (PIDS), 2018)
The main economic justification for government provision of social protection is to redistribute income to the poor, marginalized and vulnerable in society. In a developing country such as the Philippines, social protection has been a consistent priority of government. In the recent decade, there was progress in the design and delivery of social protection programs because of the adoption of a social protection strategy and framework to consolidate efforts and better target programs. Evidence of declining poverty incidence and documented improvements in the design and implementation of programs is promising. However, there is still more work to be done in terms of increasing coverage, improving implementation and coherence in social protection (World Bank 2018, 5). This study looks at how much the Philippine government has invested in social protection in recent years. It also discusses social protection programs and documents their evolution and redesign. The review highlights the importance of monitoring and evaluating programs through audits and impact assessments, in the redesign of programs.
Keywords: 330; Social protection; social safety nets; social insurance; labor market intervention; implicit subsidy